KOORDINASI PEMERINTAH DINAS PERHUBUNGAN KOTA PEKANBARU DAN SATLANTAS POLRESTA PEKANBARU DALAM PENANGANAN AKSI BALAP LIAR DI KOTA PEKANBARU TAHUN 2022-2023 - ', Monica; Hadi, Syofyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The illegal street racing action has become a serious problem that interferes with public order and threatens the safety of the people of the new Monday. The study aims to review coordination between local governments, in this case the new appellation service, the new pekansta polresta, and the regional people's representative council (DPRD) of the new pekand. The research site of a new pekanbaru city. The study USES the theory of coordination presented by Harold knootz and Cyril o 'donnel as four indicators of cooperation, meeting, good communication and task division. The study USES a descriptive qualitative approach. Data collection techniques through interviews and documenting. Studies have shown that coordination between the nexus service, the polresta department, and the new pekand city in the handling of illegal street racing is quite effective, although several challenges remain. Coordination is carried out through regular meetings and combined patrols. The DPRD has taken an active role in implementing public aspirations and encouraging more strict zoning regulations and specific budget allocations for handling the problem. Furthermore, preventive efforts such as schools socialization and cross-country safety campaigns are also a major focus. Education given to students in various schools is expected to increase awareness of the dangers of wild racing and the importance of obeying traffic rules. Keywords: cooperation, communication, meeting, task division